(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
This study aimed to evaluate the effect of organic and inorganic fertilizers on the pitaya’s Hylocereus undatus performance under field conditions. The experimental design used was Completely Randomized Block Design (CRBD). Five treatments consisting of the four different fertilizer dosages were included in this study, namely T1 (00-120-320-120); T2 (04-080-160-080); T3 (06-060-100-060); T4 (08-000-000-000) and T5 (Control: 00-000-000-000) of bovine manure (kg pit-1), urea (g pit-1), super simple (g pit-1) and potassium chloride (g pit-1), respectively. Parameters such as height, number, length, width, area, and volume of the cladodes were assessed at 20 and 320 days after planting. The number of fruits produced and mineral composition (N, K, Ca, Mg, P, and S) of H. undatus plants were also assessed. The results on morphometric characteristics of the cladodes, macronutrient composition, and fruit yield have been recorded with higher values in treatments 3 and 4. However, according to the principal component analysis performed, treatment 3 was the one that correlated with the evaluated characteristics. The results have indicated clearly the importance of combination of adequate dose of mineral and organic fertilizer for better vegetative performance and yield of pitaya crop.